(untitled) (Research, Society and Development, 2020)
This study aims to determine the use of SQ3R learning method on biology learning outcomes of students at State High School 1 Bandar the subject matter of food digestion system and determine the barriers of SQ3R learning method on biology subject of State High school 1 Bandar. This research is quantitative research. This research subject is 33 students in State High School 1 Bandar with the composition of 11 male students and 22 female students in second semester of 2018/2019 academic year. The result is implementation on learning methodology of SQ3R (Survey, Question, Read, Recite, and Review) as an effort to improve student learning outcomes on the subject material of human digestive system, consider as an effective learning method. It can be concluded that the learning outcomes of students within the application of the SQ3R learning method (Survey, Question, Read, Recite, and Review) especially on the subject matter of the human digestive system have been increased.